A strategy for successful integration of DNA-based methods in aquatic monitoring - Blancher, Philippe; Lefrançois, Estelle; Rimet, Frederic; Vasselon, Valentin; Argillier, Christine; Arle, Jens; Beja, Pedro; Boets, Pieter; Boughaba, Jeanne; Chauvin, Christian; Deacon, Michael; Duncan, Willie; et al. (My University, 2022)
Recent advances in molecular biomonitoring open new horizons for aquatic ecosystem assessment. Rapid and cost-effective methods based on organismal DNA or environmental DNA (eDNA) now offer the opportunity to produce inventories of indicator taxa that can subsequently be used to assess biodiversity and ecological quality. However, the integration of these new DNA-based methods into current monitoring practices is not straightforward, and will require coordinated actions in the coming years at national and international levels. To plan and stimulate such an integration, the European network DNAqua-Net (COST Action CA15219) brought together international experts from academia, as well as key environmental biomonitoring stakeholders from different European countries. Together, this transdisciplinary consortium developed a roadmap for implementing DNA-based methods with a focus on inland waters assessed by the EU Water Framework Directive (2000/60/EC). This was done through a series of online workshops held in April 2020, which included fifty participants, followed by extensive synthesis work. The roadmap is organised around six objectives: 1) to highlight the effectiveness and benefits of DNA-based methods, 2) develop an adaptive approach for the implementation of new methods, 3) provide guidelines and standards for best practice, 4) engage stakeholders and ensure effective knowledge transfer, 5) support the environmental biomonitoring sector to achieve the required changes, 6) steer the process and harmonise efforts at the European level. This paper provides an overview of the forum discussions and the common European views that have emerged from them, while reflecting the diversity of situations in different countries. It highlights important actions required for a successful implementation of DNA-based biomonitoring of aquatic ecosystems by 2030.
Keywords: Aquatic ecosystems; DNAqua-Net; Ecological assessment; eDNA; Water Framework Directive